Relaxação estrutural em ligas vítreas e parcialmente cristalizadas do sistema Cu-Zr-Al através da técnica de espectroscopia mecânica - Marques, Paulo Wilmar Barbosa (Universidade Federal de São Carlos, 2013)
In recent years the study of bulk metallic glasses (BMG) is being of great scientific and technological interest due to their unique properties (the lack of long range atomic order in the structure and compositional homogeneity similar to the liquid state). These alloys show better mechanical properties, superior corrosion resistance, high yield stress and fracture toughness, if compared to their crystalline counterparts. However, a physical understanding of disordered structure and how it affects the properties of metallic glasses is still considered one of the great challenges in Condensed Matter Physics and Materials Science. Since the Mechanical Spectroscopy technique is sensitive to phase transitions and dynamical processes, it provides the anelastic spectra (internal friction and oscillation frequency) as function of temperature, through which relevant informations to the understanding of structural and vibrational changes of metallic glasses are obtained. In this study, the mechanical spectroscopy technique was used to investigate dynamic processes related to elastic and electronic contributions of atomic motions and clusters, as well as other changes in the atomic bonds on the glassy and partially crystallized alloys of the ternary system Cu-Zr-Al. The samples were obtained combining criteria of the minimum topological instability and the average electronegativity (λmin∙Δē), and were investigated at temperatures above and below room temperature (300 K) with applied frequencies in Hz, kHz and MHz magnitude order. Above room temperature, the application of alternated stresses in the order of Hz and KHz allowed us to observe structural changes involving atomic rearrangements due to anelastic, viscoelastic and thermoelastic aspects present in the relaxation process. In this temperature range, the viscoelastic and thermoelastic character overlaps the anelastic relaxation mechanisms that could be observed in metallic glasses. Analysis of samples with nominal composition Cu54Zr40Al6 - nanocrystalline and vitreous - show that the anelastic relaxation processes begin below room temperature, and are dependent of the applied frequency. When the applied frequencies are in the Hz magnitude order, some clusters have their shell affected by the alternate elastic stresses. When the samples are excited with kHz order of magnitude frequencies, two well-defined relaxation centers will appear. This phenomenon is caused by the movement of clusters which are created and annihilated at the same time the stress is applied. When the applied stresses are of MHz magnitude order, the clusters are rearranged in a more efficient way, in which the less stable clusters involving Zr are annihilated and clusters with Al or Cu at their centers are reordered in order to promote the stability of the icosahedral structure embedded in the amorphous matrix. Under applied mechanical energy corresponding to the MHz frequencies, more stable structures are created and the clusters approach, interact and interpenetrate each other, giving rise to the free bond planes where the superclusters rearrange leading to the formation of medium range chains. Under persistent mechanical stimulation in MHz, the structures begin to form long-range order that lead to formation of the first crystalline precipitates. Those purely anelastic relaxation mechanisms are initiated at low temperatures, and in most cases, it´s not possible to observe them at higher temperatures due to the viscoelastic and thermoelastic character, which generally occur simultaneously in metallic glasses.
Keywords: Física da matéria condensada; Espectroscopia mecânica; Vidros metálicos; Relaxação anelástica; Atrito interno; Metais amorfos; CIENCIAS EXATAS E DA TERRA::FISICA